Overcoming Form: reflections on immersive listening - Glover, Richard; Harrison, Bryn (University of Huddersfield Press, 2013)
This short collection of essays focuses on four areas of immersive sound environments: repetition, sustained tones, performed installations and approaches to extended forms. Through in depth exploration of the experiential nature of these subjects, the authors offer reflections upon the materials used for these environments, how they are organised, and the consequences of this on how we listen.